MIM-GA: Measuring Non-Native Students’ Group Attitude (GA) in using Mobile Instant Messaging (MIM) in Learning English - Noor Raha, Mohd Radzuan; Zarina, Mohd Ali; Abdullah Adnan, Mohamed; Nurkarimah, Yusof (Asian EFL Journal Press, 2016)
Successful language learning often requires students to collaborate in a group in completing certain tasks assigned to them by instructors. The success of such collaboration relies heavily on effective communication which requires positive attitude among group members. However, group attitude can be difficult to measure. Meanwhile, technological advancement has made mobile instant messaging (MIM) very popular in group communication. Much research has been conducted on GA and increasing number of studies have shed light on MIM. Nevertheless, little is known about their relationship. Therefore, this study aimed to measure non-native students’ group attitude (GA) in using MIM in completing their English language classroom group projects and the strength of the relationship between MIM and GA. A total of 77 students participated in the study by answering a set of questionnaire comprising 35 items (20 GA items and 15 MIM items). Results have shown a significantly positive correlation between MIM and GA. Thus, it can be concluded that positive group attitude, which is key to effective group communication, can be achieved and enhanced with the use of MIM. This study further recommends that MIM should be seriously considered for implementation in English language learning in which group communication is of great importance.